Cyber-physical distributed systems modeling, reliability analysis and applications - Mo, Huadong; Sansavini, Giovanni 1981-; Xie, Min 1963- (Wiley, 2021)
CYBER-PHYSICAL DISTRIBUTED SYSTEMSGather detailed knowledge and insights into cyber-physical systems behaviors from a cutting-edge reference written by leading voices in the fieldIn Cyber-Physical Distributed Systems: Modeling, Reliability Analysis and Applications, distinguished researchers and authors Drs. Huadong Mo, Giovanni Sansavini, and Min Xie deliver a detailed exploration of the modeling and reliability analysis of cyber physical systems through applications in infrastructure and energy and power systems. The book focuses on the integrated modeling of systems that bring together physical and cyber elements and analyzing their stochastic behaviors and reliability with a view to controlling and managing them.The book offers a comprehensive treatment on the aging process and corresponding online maintenance, networked degradation, and cyber-attacks occurring in cyber-physical systems.